Long-Run Performance Evaluation of Journalists' Stock Recommendations - Alexander G. Kerl; Andreas Walter (Kredit und Kapital, 2009)
Long-Run Performance Evaluation of Journalists' Stock Recommendations This paper evaluates the long-run performance of buy and sell recommendations issued by journalists at German Personal Finance Magazines for the first time. We find evidence for journalists providing significant investment value with their recommendations on the sell side since sell recommendations contain high investment value for readers. In contrast, buy recommendations generally contain only little investment value. However, we find that journalists' predictive abilities differ with respect to specific types of buy recommendations. On the one hand, buy recommendations on value stocks and stocks with a positive performance prior to the publication date are associated with significant investment value for readers. On the other hand, executing buy recommendations on stocks listed at the Neuer Markt would have resulted in serious losses for private investors. (JEL G11, G14) – – Langfristige Performance von Aktienempfehlungen deutscher Börsenmagazine Der vorliegende Aufsatz untersucht erstmalig die langfristige Renditeentwicklung von Kauf- und Verkaufsempfehlungen deutscher Anlegermagazine. Die Untersuchungsergebnisse legen nahe, dass die Empfehlungen der Journalisten werthaltig sind. Insbesondere ist das Befolgen von Verkaufsempfehlungen anzuraten. Kaufempfehlungen verfügen hingegen im Allgemeinen lediglich über geringen Wert für Privatanleger. Allerdings zeigen die Journalisten besondere prognostische Fähigkeiten bei einzelnen Typen von Aktien. So lassen sich mit Kaufempfehlungen für Substanzaktien und für Aktien mit einem positiven Renditemomentum signifikante Überrenditen erwirtschaften.
Keywords: G11; G14; 330